A model for documenting architectural decisions - Roldán, María Luciana (2013)
A software architecture is the result of architectural design decisions. Documenting a software architecture should not only describe the final model, but also why the architecture looks as it does. During the software architecture design process, several decisions are made, which need to be captured and documented in a systematic way to prevent knowledge vaporization and high architecture’ costs of change. In this work, a model for capturing, documenting and recovering architectural design processes and their underlying design rationale is proposed. The design process is envisioned under an operational perspective, where design decisions are represented as sequences of operations. Besides, the model is extensible to manage several design products types from different domains and views, including aspects of architectural rationale. Complementary, the proposal provides a semi-automatic mechanism for generating architectural rationale documents based on the use of templates.